Raziskave na področju slovenskega narodnega vprašanja v Sloveniji po letu 1990 - Klemenčič, Matjaž (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2006)
RESEARCH ON SLOVENE NATIONAL QUESTION IN SLOVENIA AFTER 1990. Institute for Ethnic Studies (IES) is one of the oldest European scholarly institutions in which scholars almost exclusively deal with issues connected with ethnic, especially minority questions. Researchers devote their interdisciplinary research work to numerous and varied issues in research of the past and present of Slovene autochthonous minorities in the neighboring countries, of both autochthonous ethnic minorities in Slovenia (Italians, Hungarians), and Slovene ethnic communities outside Slovene ethnic territories. Researchers devote their time also to research on Roma, as well as to history of Germans in the present Republic of Slovenia. After Slovenia became an independent state, it became very popular to do research on so-called "new minorities", i.e. immigrants to Slovenia. They represent on the one hand immigrant communities from the former Yugoslav republics who settled in Slovenia en masse from 1960s onward, and on the other hand they represent also those ethnic groups who settled in Slovenia after it gained independence in 1991. Besides the IES there are also other institutions in Slovenia in which researchers do similar research, i.e. universities in Ljubljana, Maribor, and Koper; different institutes of the Scientific Research Center of Slovene Academy of Arts and Sciences in Ljubljana, the Institute for Contemporary History, etc. Very significant is also research done by research institutes sponsored by different organizations of Slovene minorities in Austria, Italy, and Hungary. The results are numerous books and scientific articles published in numerous international and Slovene reviews and other publications. The IES researchers alone have since 1990 published more then 200 articles and 6 books outside of the Slovene ethnic territories.
Keywords: raziskovalni inštituti; Inštitut za narodnostna vprašanja (Ljubljana); raziskovalci; narodne manjšine; narodnostno vprašanje; zgodovinski pregledi